Adverse childhood experiences and allostatic load in adolescence and emerging adulthood - French, Kate M., author; Lucas-Thompson, Rachel, advisor; Graham, Dan, committee member; Shomaker, Lauren, committee member (Colorado State University. Libraries, 2017)
Adverse childhood experiences (ACEs), which include experiences of abuse, neglect, and household dysfunction, have been shown to be associated with increased occurrence of a number of diseases and risk behaviors in later adulthood (Felitti et al., 1998). In an effort to explain how adversity in childhood is related to later disease, the theoretical framework of allostasis and allostatic load (AL) is often employed (Danese & McEwen, 2012). In this context, it is postulated that the body responds adaptively to a variety of psychosocial stressors in a multi-systemic fashion (McEwen, 1998). The nervous, endocrine, and immune systems act and interact to respond to stressors in a way that allows the body to mobilize the resources necessary to remain safe in the face of threats and recover from that mobilization in a way that promotes physiologically balanced state of allostasis. However, repeated or chronic stressors can overwhelm the body's ability to respond toward long-term adaptation, and the body enters a state of AL. Dysregulated stress responses are a hallmark of allostatic load and can impair the body's ability to mobilize resources or recover from stressors efficiently leading to an imbalance of multiple physiologic responses. This imbalance is thought to cause "wear and tear" on the body, leading to later disease (McEwen, 1998). Although these dysregulated stress responses and the resulting physiological imbalances are thought to begin in childhood and continue throughout adolescence and emerging adulthood as well as in adults, little empirical research has been done with participants in these developmentally sensitive periods. In this study, a community sample (n = 114) of adolescents and emerging adults self-reported the ACEs they had experienced. An AL summary score was calculated by assigning scores to the highest risk quartiles of body mass index, blood pressure, self-rated health, baseline heart rate, and change in heart rate in response to a psychosocial stressor. ACE scores were compared with AL indices and the AL summary score along with age, sex, ethnicity, family income, and maternal support. Bivariate analyses indicated that ACEs were positively associated with body mass index, baseline heart rate, and age; and negatively associated with maternal support. When controlling for age, sex, ethnicity, family income, and maternal support in a multiple regression analysis, the positive association between ACEs and baseline heart rate remained such that participants who reported more ACEs had higher baseline heart rates. The results of this study indicate a need for further investigation between ACEs and AL indices including indications of dysregulated stress responses. Additionally, the negative association between ACEs and maternal support deserves further research attention.